DISTRIBUTION OF BENEFITS OF COMMUNITY-BASED CLEAN WATER INFRASTRUCTURE PROVISION - Akbar Rinda, Zuhallfi
Infrastructure serves as a vital connector within a region, influencing economic, social, and environmental activities. Although infrastructure development provides significant benefits, these benefits are often unevenly distributed, particularly in rural and peripheral areas. In developing countries, infrastructure tends to focus on urban areas, creating economic and social inequality. This research highlights the importance of community-based infrastructure, which ensures solutions that meet local needs and distribute benefits more equitably. Given the limited research on the distribution of benefits from community-based clean water infrastructure, this study aims to understand the benefit distribution of community-based clean water infrastructure and the factors influencing it. Identifying the distribution of benefits is assisted by descriptive statistical analysis and literature review analysis, while identifying influencing factors uses multiple linear regression analysis to examine the variables that significantly affect the distribution of benefits. The analysis results indicate that in the study area, the distribution of benefits from clean water provision is still uneven or equitable but with negative benefits. Thus, based on these findings, it is known that the provision of community-based clean water infrastructure is still unfairly distributed for some groups, particularly those in the lower-middle economic class.